2019
DOI: 10.26434/chemrxiv.11323571.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping Solvation Heterogeneity in Live Cells by Hyperspectral Stimulated Raman Scattering Microscopy

Abstract: Water provides a dynamic matrix in which all biochemical processes occur in living organisms. The structure and dynamics of intracellular water constitute the cornerstone for understanding all aspects of cellular function. Fundamentally, direct visualization of subcellular solvation heterogeneity is essential but remains challenging with commonly used NMR methods due to poor spatial resolution. To explore this question, we demonstrate a vibrational-shift imaging approach by combining the spectral-focusing hype… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In addition, studies have shown that ASE can also act as Raman seed light to cause Raman amplification, leading to a reduction in the SRS threshold. Lang et al [33] investigated the effect of Raman scattering noise in the seed light on the SRS and gave a formula for calculating the Raman threshold of high-power amplifier when considering Raman scattering noise in the seed light, showing that when the Raman scattering noise in the seed light is greater than 10-8 W, it plays an important role in the Raman threshold of the high-power amplifier.…”
Section: Transmission Analysis Based On Seed Characteristicsmentioning
confidence: 99%
“…In addition, studies have shown that ASE can also act as Raman seed light to cause Raman amplification, leading to a reduction in the SRS threshold. Lang et al [33] investigated the effect of Raman scattering noise in the seed light on the SRS and gave a formula for calculating the Raman threshold of high-power amplifier when considering Raman scattering noise in the seed light, showing that when the Raman scattering noise in the seed light is greater than 10-8 W, it plays an important role in the Raman threshold of the high-power amplifier.…”
Section: Transmission Analysis Based On Seed Characteristicsmentioning
confidence: 99%
“…Compared to previous study of limonene biosynthesis detection by single-color SRS (25,26), hSRS allows simultaneous quantification of multiple chemicals inside one specimen by recording a Raman spectrum at each pixel. Intracellular compositions of various biological specimens have been studied using hSRS, ranging from tissues (27,28), to cancerous cells (29,30), to bacteria (31,32). Many of these applications employ the C-H stretching region (2800 -3100 cm -1 ) for its strong SRS signal or the C-D stretching region (2070 -2300 cm -1 ) for selective imaging of Raman tags.…”
Section: Introductionmentioning
confidence: 99%